Aspartame and Phenylketonuria: an analysis of the daily phenylalanine intake of aspartame-containing drugs marketed in France - Maler, Victor; Goetz, Violette; Tardieu, Marine; Khalil, Abderrahmane El; Alili, Jean Meidi; Meunier, Philippe; Maillot, François; Labarthe, François (Orphanet journal of rare diseases, 2023)
Background Phenylketonuria (PKU) is a rare genetic metabolic disorder in which especially high phenylalanine (Phe) concentrations cause brain dysfunction. If untreated, this brain dysfunction results in severe microcephaly, intellectual disability, and behavioral problems. Dietary restriction of Phe is the mainstay of PKU treatment, with long-term successful outcomes. Aspartame, an artificial sweetener sometimes added into medications, is metabolized in the gut into Phe. Then, patients suffering from PKU on a Phe-restricted diet should avoid consumption of aspartame. The aim of our study was to evaluate the number of drugs containing aspartame and/or Phe as an excipient, and to quantify their corresponding Phe intake. Methods The list of drugs marketed in France containing aspartame and/or Phe was established using a national medication database called “Theriaque”. For each drug, the corresponding daily Phe intake was calculated according to age and weight and was distributed into 3 categories: high (> 40 mg/d), medium (10 to 40 mg/d) and low (< 10 mg/d) Phe intake. Results The number of drugs containing Phe or its precursor aspartame remained very limited ( n = 401). Among the aspartame containing drugs, Phe intakes were significant (medium or high) for only half of them whereas there were negligible for the others. Furthermore, these medications with a significant Phe intake were limited to few pharmaceutical classes (mainly antiinfectives agents, analgesics, and drugs for nervous system), and within these classes the drugs were limited to a small number of molecules, including principally amoxicillin, amoxicillin + clavulanic acid and paracetamol/ acetaminophen. Discussion In situations requiring the use of these molecules, we propose as an alternative, the use of an aspartame-free form of these molecules or a form with a low Phe intake. If it is not possible, we propose as second-line the use of another antibiotics or analgesics. Finally, we have to remember the benefits-risk balance to use medications containing significant Phe intake in PKU patients. Indeed, it may be better to use a Phe containing medication in the absence of an aspartame-free form of this drug rather than to leave a person with PKU without treatment.